1979
DOI: 10.1021/ja00503a035
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 NMR spectroscopy of [20%-1,2-13C2-Gly6]-bradykinin. Role of serine in reducing structural heterogeneity

Abstract: Substitution of a glycine residue for the serine residue at position six in the nonapeptide bradykinin leads to a dramatic increase in the cis/trans ratio about the sixth peptide bond (~38% cis). Decreases in the cis/trans ratio determined by NMR in 1 M NaC104 and in 60% ,2CH30H have been correlated with decreases in the 219-nm CD band. Chemical shifts of the 20% 13C-labeled Gly6 residue exhibit a very different pattern from that observed in the dipeptide Gly-L-Pro; the cis-trans shift difference is ~0 ppm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 2 publications
(2 reference statements)
1
14
0
Order By: Relevance
“…However, the starting material is never isotopically pure, so that the resulting compounds such as amino acids, sugars, fatty acids, and even proteins and viruses must also be only partially enriched. It has been assumed in the past that isotopically labelled compounds of biosynthetic origin i) are statistically enriched, and ii) show a uniform enrichment factor [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the starting material is never isotopically pure, so that the resulting compounds such as amino acids, sugars, fatty acids, and even proteins and viruses must also be only partially enriched. It has been assumed in the past that isotopically labelled compounds of biosynthetic origin i) are statistically enriched, and ii) show a uniform enrichment factor [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of three prolines in the sequence is expected to yield structural heterogeneity in solution, because the cis trans interconversion at each X–Pro bond may provide up to eight stable isomers, depending on environmental parameters. Several CD and NMR investigations in a number of solvent systems have occasionally detected transient ordered structures, similar to γ turns and β turns [6–23]; however, the net result of a random coil peptide was obtained in all cases due to the fast rate of exchange between the extended structures. Such a high degree of flexibility suggests that binding to the receptor implies the selection of a particular structure from among the number of slowly or rapidly interconverting ones in solution.…”
mentioning
confidence: 99%
“…The substitution of a glycine residue for Ser6 of bradykinin significantly increases the cis/trans ratio about the sixth peptide bond from ~0.1 to ~0.4 (London et al, 1979). The physical basis for this effect has been analyzed in detail on the basis of chemical shift, coupling constant, and relaxation data of model peptides and results primarily from an unfavorable interaction between the Phe8 side chain and the Gly6 carbonyl oxygen in the trans configuration (Anteunis et al, 1981).…”
Section: Resultsmentioning
confidence: 99%
“…Arg-Pro-Pro-Gly-Phe-Ser-Pro-Phe-Arg) and the test peptides which have been used to study cyclophilin-catalyzed cis/trans isomerization (Fischer et al, 1984(Fischer et al, , 1989aTakahashi et al, 1989;Harrison & Stein, 1990), it was of interest to determine whether this biologically active peptide is also a substrate for cyclophilin. We have previously noted that, despite a strong preference for the trans conformation of all X-Pro bonds in bradykinin, a large increase in the cis/trans ratio of the sixth peptide bond, in addition to a small decrease in activity, results from the substitution of a Gly6 residue for the native Ser6 (London et al, 1979). On this basis, we have suggested that the predominant trans conformer is most probably the biologically active form of the peptide and that a principle role of Ser6 is to favor the proportion in the trans conformation.…”
mentioning
confidence: 99%